2018
DOI: 10.1055/a-0751-2886
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous K-wires vs palmar locking plate fixation for different types of distal radial fractures: a comparison of the outcomes of two methods to controll our guidelines

Abstract: The objective of the study was a comparison of the outcomes of K-wire vs plate fixation for distal radial fractures used according to the proposed institutional algorithm. Fracture configurations A2, A3, B1, B2, C1 and some C2 were operated on with K-wire pinning, whereas B3 and some B2, C3 and some C2 were with locking palmar-plate fixation. Patients and Methods: Four hundred and sixty-seven patients were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…14 Zyluk et al observed volar tilt angles closer to normal ones in a group with volar plate fixation and K-wire stabilization. 19 The mean post-treatment volar tilt angles reported by Zengin et al were within the adopted normal range in patients treated with volar plate fixation (6.9°) but fell outside of the normal range (−1°) in patients treated with cast immobilization. 15 In our study, volar tilt values closer to normal were observed in the 6-week group, whereas values different from the normal ones were noticed in the 4-week group.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…14 Zyluk et al observed volar tilt angles closer to normal ones in a group with volar plate fixation and K-wire stabilization. 19 The mean post-treatment volar tilt angles reported by Zengin et al were within the adopted normal range in patients treated with volar plate fixation (6.9°) but fell outside of the normal range (−1°) in patients treated with cast immobilization. 15 In our study, volar tilt values closer to normal were observed in the 6-week group, whereas values different from the normal ones were noticed in the 4-week group.…”
Section: Discussionmentioning
confidence: 85%
“…The volar tilt angle values in our study were similar to those of other studies. 7,9,[13][14][15]19 The mean radial height value in DRF patients treated with cast fixation was 3.9-9.0 mm, depending on the group. 9,[13][14][15] In our study, both groups achieved radial height values close to normal.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Moreover, oblique Kapandji K-wires engaging a single cortical wall risk wire migration, especially in oblique and comminuted fractures. Its stability depends on the correct wire position, a good fracture pattern, intact cortical wall, and good bone quality, but these factors may be compromised due to the lack of direct visualization of the tissue and fracture site 10 . These drawbacks prompted us to modify the xation technique.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, oblique Kapandji K-wires engaging a single cortical wall risk wire migration, especially in oblique and comminuted fractures. The stability depends on proper wire placement, fracture patterns, intact cortical walls, and good bone quality, but these factors may be affected by the inability to visualize the soft tissues and fracture site [ 10 ]. Those drawbacks prompted us to modify the fixation technique.…”
Section: Introductionmentioning
confidence: 99%